PERKEMBANGAN SENI UKIR BALI PADA MASYARAKAT TRANSMIGRASI DI PROVINSI SULAWESI TENGAH - Sudana, I Wayan; Roi Andreawan, I Wayan Roi; Hasmah, Hasmah (Universitas Negeri Makassar, 2025)
This study aims to reveal the development of Balinese carving art in transmigration communities in Central Sulawesi along with the factors that influence it. The study used a qualitative method with a historical approach. Data were collected through observation, interviews, and document studies. Data analysis was carried out interactively through data reduction, data display, and drawing conclusions. The results show that the development of Balinese carving art in transmigration communities in Central Sulawesi occurred in four periods. Period I (1976-1990), carvings in the form of plant motifs, function as decoration. Period II (1990-2010), carving art in the form of plant motifs, animal motifs, human motifs, and imagination motifs. Functions as decoration, symbolic and economic. Period III (2010-2015), carvings in the form of plant motifs, animal motifs, human motifs, imaginative motifs, symbolic motifs. Functions as decoration, symbolic, spiritual, social status, economic. market commodities. Period IV (2015-2023), carvings in the form of geometric motifs, plant motifs, animal motifs, human motifs, imaginative motifs, symbolic motifs. Functions as decoration, symbolic, spiritual, social status, economy, market commodities. Internal and external factors that influence this development are the skills and creativity of the carver, aesthetic value, economic needs, and market demand. It is concluded that Balinese carvings in transmigration communities in Central Sulawesi have experienced dynamic developments influenced by various mutually supportive factors